MEASUREMENT OF PHYSICS EDUCATION STUDENTS’ PROBLEM-SOLVING ABILITY ON CHEMICAL BONDING AND MOLECULAR SHAPE TOPICS - Nopriawan Berkat Asi; Siska Alvionita; Deklin Frantius; Triliyansi (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2025)
This study aims to measure the problem-solving ability of Physics Education students on the topic of chemical bonding and molecular shape in the Basic Chemistry course. The measurement was conducted in December 2024 using 20 essay-type questions developed based on Polya’s problem-solving indicators: understanding the problem, devising a plan, carrying out the strategy, and evaluating the result. The research subjects consisted of 12 students enrolled in the Basic Chemistry course. Data were analyzed quantitatively using descriptive statistics by calculating the percentage of achievement for each indicator. The results showed that the students’ problem-solving abilities varied across the indicators. The average achievement scores were 75.40% for understanding the problem (good category), 69.20% for devising a plan (fairly good category), 67.50% for carrying out the strategy (fairly good category), and 59.60% for evaluating the result (poor category). These findings indicate that students were relatively capable of understanding problems and planning solutions, but they still faced difficulties in consistently implementing strategies and were particularly weak in evaluating their results. In conclusion, the problem-solving ability of Physics Education students on the topic of chemical bonding and molecular shape was generally in the fairly good category, with the main weakness found in the evaluation stage. This study recommends the implementation of learning strategies that emphasize reflection and answer verification, such as problem-based or inquiry-based learning models, to enhance students’ problem-solving skills more comprehensively.